Faktor-faktor yang Mempengaruhi Efektivitas Fungsi Audit Internal pada Pemerintah Daerah X - Faiz Zamzami; Rumiyati Rumiyati; Rudi Prasetya Timur (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The professional challenge of internal auditors in Indonesia is how to provide added value to the organization, especially in ensuring the implementation of good governance and organizational risk management. The limited research in the field of internal audit in local governments in Indonesia has become the main urgency in this study. The purpose of this study is to examine the effect of cooperation between internal and external auditors; management support; effectiveness of internal controls; and auditor experience on the effectiveness of internal audits. This study uses a survey method with a research instrument in the form of a questionnaire. 58 research respondents were auditors and financial staff who worked at the Regional Inspectorate and Financial and Asset Agency (BKAD) in Local Government. The data analysis method used in this study was multiple regression. The results of the study state that management support and auditor experience affect the effectiveness of internal auditors. Whereas, the collaboration between the auditor's internal and external auditors and the effectiveness of internal controls does not affect the effectiveness of internal auditors.